Families, time and well-being in Canada - Peter Burton; Shelley Phipps (Luxembourg Income Study (LIS), 2010)
Using cross-sections of microdata from Surveys of Consumer Finance and Surveys of Labour and Income Dynamics, we document changes in the availability of time and money in Canadian two-parent families between 1971 and 2006 as the paid work hours of mothers have increased. While long hours of paid work were mostly characteristic of higher-income families during the 1970's, by 2006 over half of families supplying more than 80 paid hours are from the bottom half of the income distribution. Between 1994 and 2006, the largest increases in paid hours have occurred in middle and lower-middle income families; these families have not experienced similarly large increases in real income. Canadian time use data from 1992 and 2006 confirm larger increases in parental time stress for low-income than for high-income families. Since, controlling income, high paid work hours are negatively correlated with life satisfaction, our results suggest that inequality of well-being may have increased even more than inequality of income over recent decades. While some policy attention has been directed at supporting incomes of modest income families with children, we identify a policy gap in alleviating time pressures for these families, after the first year.
Keywords: I3; J1; J22; 330; family; inequality; well-being; life satisfaction; happiness; time crunch; Familienökonomik; Zeitökonomie; Lebensqualität; Zufriedenheit; Kanada